2023
DOI: 10.3390/antiox12040978
|View full text |Cite
|
Sign up to set email alerts
|

The Prebiotic Effects of an Extract with Antioxidant Properties from Morus alba L. Contribute to Ameliorate High-Fat Diet-Induced Obesity in Mice

Abstract: Obesity is a global health issue, in which modifications in gut microbiota composition have a key role. Different therapeutic strategies are being developed in combination with diet and exercise, including the use of plant extracts, such as those obtained from Morus alba L. leaves. Recent studies have revealed their anti-inflammatory and antioxidant properties. The aim of the present work was to evaluate whether the beneficial effects of M. alba L. leaf extract in high-fat diet-induced obesity in mice is corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…On the other hand, some authors attributed metabolic deregulations and oxidative stress to changes in the intestinal microbiota composition caused by high-fat or high-fructose diets. Thus, ameliorative effects could be related to the prebiotic character of some polyphenols [ 42 , 43 , 44 ]. In fact, in a previous study, chia defatted flour showed positive effects on the intestinal microbiota using an in vitro gastrointestinal digestion model (increasing Lactobacillus and decreasing Enterobacteriaceae ) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors attributed metabolic deregulations and oxidative stress to changes in the intestinal microbiota composition caused by high-fat or high-fructose diets. Thus, ameliorative effects could be related to the prebiotic character of some polyphenols [ 42 , 43 , 44 ]. In fact, in a previous study, chia defatted flour showed positive effects on the intestinal microbiota using an in vitro gastrointestinal digestion model (increasing Lactobacillus and decreasing Enterobacteriaceae ) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%